Sustainable High-Rise Buildings: Toward Resilient Built Environment - Al-Kodmany, Kheir (Frontiers in Sustainable Cities, 2022)
Increasingly, architects and engineers are interested in pursuing sustainable design. Yet, they lack sources that summarize best practices. As such, this review paper maps out and examines prominent examples of "sustainable" skyscrapers of varying geographic locations, climates, and socio-cultural contexts. It discusses the design themes and green features of "LEED skyscrapers" and elaborates on recent developments in architecture and engineering. The presented 12 case studies do not intend to evaluate LEED rating systems. Instead, they illustrate how LEED has advanced the green design agenda and encouraged the pursuit of innovative design and engineering solutions. The mapped-out green features in this article should be helpful to all professionals interested in green architecture.